PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X MIA SMAN 1 BANGUN PURBA TAHUN PELAJARAN 2014/2015 - -, Asnawiyah; Afri, Lusi Eka; -, arcat (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of this study was to determine whether there was an effect of cooperative learning Numbered Head Together (NHT) on learning outcomes math class X MIA SMAN 1 Bangun Purba in academis years 2014/2015. The research was a quasi-experimental study with randomized study design Posttest Only Control Group Design. The population in this study were students of class X MIA SMAN 1 Bangun Purba consist of two classes of grade X MIA 1 and X MIA 2. The sampling was did by used saturated sample, then the determination of the experimental class and the control class was did by lottery, were selected as the experimental class was a class X MIA 2 whereas for the control class was the class X MIA 1. The instrument of this study was to learn the test results. For data analyzed of learning outcomes, researchers used was the t test. From the analysis of data it could be concluded that there was an effect of cooperative learning Numbered Head Together (NHT) for mathematics learning outcomes of students of class X MIA SMAN 1 Bangun Purba in academic years 2014/2015